Assessment of the airborne sound insulation from mobility vibration measurements; a hybrid experimental numerical approach. (13th October 2018) - Roozen, N.B.; Leclère, Q.; Urbán, D.; Méndez Echenagucia, T.; Block, P.; Rychtáriková, M.; Glorieux, C.
Abstract: A new measurement procedure is proposed to assess the airborne sound insulation of a partition under diffuse sound field excitation using mobility measurements combined with a numerical procedure. The advantage of this hybrid approach is that the diffuse acoustic field does not need to be physically created, thus avoiding problems related to the generation of such fields at low frequencies. Furthermore, the acoustic properties of both the source and receiving rooms will not affect the determination of the sound reduction index R . The proposed method is especially suited for frequencies below the so called Schroeder frequency of the room, and is complementary to the standardized measurement approaches as described in ISO 10140-2:2010. The measurement part of the proposed procedure involves the measurement of the mobility by forcing the partition along a grid of excitation points (e.g. by means of a shaker) and measuring its response along a grid of response points (e.g. by means of a scanning laser Doppler vibrometer). Using the resulting matrix of mobility transfer functions, the vibrational response of the partition excited by a diffuse acoustic field is numerically calculated, from which the radiated sound power is computed using the Rayleigh integral. Thus the reliance on source and receiving rooms used in standard sound insulation testing is removed entirely. The proposed method provides an estimate that only depends on the properties of the partition. The method was tested in an acoustic laboratory on a single layer glass plate of 1.35 × 1.54 m 2, as well as on a funicular shell structure with dimensions of 3 × 3 m 2 . Comparisons with analytical models and standardized ISO10140-2:2010 measurements confirm the validity of the results.